A new species of Tillandsia (Bromeliaceae) from western Mexico - Espejo Serna, Adolfo; López-Ferrari, Ana Rosa (Instituto de Ecología, A.C., 2005)
Tillandsia macvaughii known from the states of Jalisco and Michoacán, Mexico, is described and illustrated. The new species is compared with T. marabascoensis Ehlers et Lautner, T. maritima Matuda and T. rothii Rauh, species with similar characteristics. An identification key, and a distribution map are included.